Legal Guarantees For Fishermen's Work Risks - Faisal Riza; Ramlan Ramlan (Universitas Muhammadiyah Sumatera Utara, 2023)
The insurance program for fishermen must be continued and developed to guarantee the future life of fishermen's families. Currently the government has provided insurance policies to fishermen from Sabang to Merauke. Fishermen's Insurance Premium Assistance is considered very important, to guarantee fishermen who die and disappear on the high seas while working. Fishermen need to be guaranteed protection for their lives and work accidents they experience, the impact of that is that fishermen's families and even fishermen themselves have the confidence to carry out their activities at sea. The form of government attention in carrying out an effort aimed at protecting fishermen and their families through the provision of the Insurance Premium Assistance Program for Fishermen (BPAN). Law of the Republic of Indonesia Number 07 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Farmers and Salt Farmers has regulated the provision of protection for work risks experienced by fishermen through the provision of insurance. Providing insurance through the Insurance Premium Assistance Program for Fishermen (BPAN) is a program to guarantee better fishermen's activities in the fishing business, so that the rights and obligations of fishermen become clear and will be protected in their fishing business activities. However, the fishermen's insurance premium assistance program is still not running effectively, many fishermen do not know about it and the implementation of socialization has not been evenly distributed. As a result, fishermen do not know how to be registered as beneficiaries of fishermen's insurance benefits, how much they actually have to get and how to get it (claims) if they experience risks in working as fishermen